(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To construct a paradigmatic classification proposal, contextualized in the Costa Rican reality, based on the sociohistorical development of theoretical approaches to vocational guidance. Methodology: A critical literature review is used, which seeks to synthesize and analyze materials from diverse sources to present a proposed paradigmatic classification model for vocational approaches. For this purpose, paradigmatic classifications from reference authors were sought, and three specific proposals were analyzed: Savickas (2012), Rascovan (2013), and McMahon (2014). Results: Among the main results, it stands out that the highlighted proposals of McMahon and Rascovan classify vocational approaches into four paradigms, while Savickas classifies them into three paradigms. Furthermore, all proposals identify a psychometric paradigm as the starting point for vocational guidance, while the social justice and career education paradigms are presented in two of the three classifications analyzed. In turn, each proposal identifies the most recent paradigm with a different name (life design, critical, complex, and new trends, respectively). Based on the study’s methodology, a proposal for an integrative model for Costa Rica is presented, consisting of five paradigms (positivism, naturalism, constructivism, sociocritical, and complex), including paradigmatic overlaps. As part of the study, the approaches within this proposal are classified. Conclusions: The paradigmatic situation of guidance in Costa Rica is located right in the middle of the current proposal from the global north (constructivist paradigm) and the Latin American one (sociocritical paradigm).